Pharmacophore-guided repurposing of fibrates and retinoids as GPR40 allosteric ligands with activity on insulin release - Erika Cione; Maria Cristina Caroleo; Hiroyuki Kagechika; Fabrizio Manetti (Taylor & Francis Group, 2021)
A classical drug repurposing approach was applied to find new putative GPR40 allosteric binders. A two-step computational protocol was set up, based on an initial pharmacophoric-based virtual screening of the DrugBank database of known drugs, followed by docking simulations to confirm the interactions between the prioritised compounds and GPR40. The best-ranked entries showed binding poses comparable to that of TAK-875, a known allosteric agonist of GPR40. Three of them (tazarotenic acid, bezafibrate, and efaproxiral) affect insulin secretion in pancreatic INS-1 832/13 β-cells with EC50 in the nanomolar concentration (5.73, 14.2, and 13.5 nM, respectively). Given the involvement of GPR40 in type 2 diabetes, the new GPR40 modulators represent a promising tool for therapeutic intervention towards this disease. The ability to affect GPR40 was further assessed in human breast cancer MCF-7 cells in which this receptor positively regulates growth activities (EC50 values were 5.6, 21, and 14 nM, respectively).